Distribution and morphological pattern of clefts in the craniofacial region seen in a sub-saharan tertiary hospital (2015)
Aim: Clefts in the craniofacial region are one of the commonest congenital anomalies recorded in literature. The incidence varies globally with racial differences observed. In Nigeria, the evaluation of the absolute incidence of oral clefts is a challenge as births and deaths are not adequately registered. Especially lacking is the relative prevalence of rare craniofacial clefts to the more common cleft lip and palate anomaly. This study aims to document the pattern of distribution of craniofacial clefts, including cleft lip and palate anomaly, rare craniofacial clefts, unusual presentation of some of these anomalies, as well as other abnormalities noted in affected cleft patients seen at our centre. Material and methods: Information on age, gender, weight at presentation, type of cleft anomaly, other abnormalities, as well as affected relatives were extracted from the clinic records of the Cleft Clinic of the University College Hospital, Ibadan, Oyo, Nigeria, from April 2010 to September 2012. Results: One hundred and forty-two cases were seen within the 30-month period, consisting of 58 men and 84 women with a mean age of 43.54 months and a median of 2.0 months. Eighty-eight per cent of the cases were cleft lip and palate anomalies, while 12.0% were craniofacial clefts. Thirteen per cent had other abnormalities, while 3.5% were considered to be unusual cleft anomalies. Conclusion: The pattern of distribution of clefts in the craniofacial region in our centre has been documented. Cleft of the primary palate was the commonest while rare craniofacial clefts constituted about one-eighth of all the craniofacial clefts.